THE DYNAMICS OF RESPIRATORY SYSTEM FUNCTION IN SCHOOLCHILDREN UNDER THE INFLUENCE OF KHATKA-YOGA HEALTH-IMPROVING GYMNASTICS - Chepurna, V.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The article includes the experimental research of Khatka-Yoga health-improving gymnastics influence to the dynamics activities function of respiratory system of schoolchildren. It is shown effectiveness of the Khatka-Yoga health-improving gymnastics.